Biomechanical Analysis of an Anterior Cervical Discectomy and Fusion Pseudarthrosis Model Revised With Machined Interfacet Allograft Spacers. Issue 8 (December 2020) - Hah, Raymond J.; Alluri, Ram; Anderson, Paul A.
Study Design: Biomechanics study. Objectives: To evaluate the biomechanical advantage of interfacet allograft spacers in an unstable single-level and 2-level anterior cervical discectomy and fusion (ACDF) pseudoarthrosis model. Methods: Nine single-level and 8 two-level ACDF constructs were tested. Range of motion in flexion-extension (FE), lateral bending (LB), and axial rotation (AR) at 1.5 N m were collected in 4 testing configurations: (1) intact spine, (2) ACDF with interbody graft and plate/screw, (3) ACDF with interbody graft and plate/loosened screws (loose condition), and (4) ACDF with interbody graft and plate/loosened screws supplemented with interfacet allograft spacers (rescue condition). Results: All fixation configurations resulted in statistically significant decreases in range of motion in all bending planes compared with the intact spine ( P < .05). One Level. Performing ACDF with interbody graft and plate on the intact spine reduced FE, LB, and AR 60.0%, 64.9%, and 72.9%, respectively. Loosening the ACDF screws decreased these reductions to 40.9%, 44.6%, and 52.1%. The addition of interfacet allograft spacers to the loose condition increased these reductions to 74.0%, 84.1%, and 82.1%. Two Level . Performing ACDF with interbody graft and plate on the intact spine reduced FE, LB, and AR 72.0%, 71.1%, and 71.2%, respectively. Loosening the ACDF screws decreased these reductions to 55.4%, 55.3%, and 51.3%. The addition of interfacet allograft spacers to the loose condition significantly increased these reductions to 82.6%, 91.2%, and 89.3% ( P < .05). Conclusions: Supplementation of a loose ACDF construct (pseudarthrosis model) with interfacet allograft spacers significantly increases stability and has potential applications in treating cervical pseudarthrosis.